Regulatory Effects of Histone Deacetylase Inhibitors on Myeloid-Derived Suppressor Cells - Cui, Yudan; Cai, Jingshan; Wang, Wenxin; Wang, Shengjun (Frontiers in Immunology, 2021)
Histone deacetylase inhibitors (HDACIs) are antitumor drugs that are being developed for use in clinical settings. HDACIs enhance histone or nonhistone acetylation and promote gene transcription via epigenetic regulation. Importantly, these drugs have cytotoxic or cytostatic properties and can directly inhibit tumor cells. However, how HDACIs regulate immunocytes in the tumor microenvironment, such as myeloid-derived suppressor cells (MDSCs), has yet to be elucidated. In this review, we summarize the effects of different HDACIs on the immunosuppressive function and expansion of MDSCs based on the findings of relevant studies.